2001
DOI: 10.1021/la001655g
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Dynamic Supraparticle Structures in Microchannels

Abstract: Paramagnetic particles in microchannels form dynamic and reversible self-assembled regularly spaced structures when exposed to an external magnetic field. The magnetically induced micron-scale patterns can be formed and reformed spontaneously, thus providing an alternative to traditional microfabrication techniques for pattern creation. Under the influence of a varying magnetic field, these structures could be rotated through all axes without loss of structural form allowing dynamic micron-scale movement witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 35 publications
0
71
0
Order By: Relevance
“…Despite its potential for magnetic-bead-based applications, only a few works are reported on the active manipulation of SPS composed from superparamagnetic particles inside microfluidic capillaries. Under the influence of a varying magnetic field generated by a mechanically moving permanent magnet, magnetic SPS composed of 1-2-lm diameter superparamagnetic beads could be rotated through all axes in a microfluidic channel, without loss of structural form, allowing dynamic micron-scale movement without direct mechanical, electrical, or photonic interactions (Hayes et al 2001a). A number of potential applications of this phenomenon were mentioned in this paper, like binding biomolecules on the magnetic particles for immuno-assays, studying subcellular biomechanics, and microfluidic mixing in picoliter and femtoliter volumes.…”
Section: Dynamic Manipulation Of Magnetic Supraparticle Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its potential for magnetic-bead-based applications, only a few works are reported on the active manipulation of SPS composed from superparamagnetic particles inside microfluidic capillaries. Under the influence of a varying magnetic field generated by a mechanically moving permanent magnet, magnetic SPS composed of 1-2-lm diameter superparamagnetic beads could be rotated through all axes in a microfluidic channel, without loss of structural form, allowing dynamic micron-scale movement without direct mechanical, electrical, or photonic interactions (Hayes et al 2001a). A number of potential applications of this phenomenon were mentioned in this paper, like binding biomolecules on the magnetic particles for immuno-assays, studying subcellular biomechanics, and microfluidic mixing in picoliter and femtoliter volumes.…”
Section: Dynamic Manipulation Of Magnetic Supraparticle Structuresmentioning
confidence: 99%
“…2 a Schematic diagram of a spherical magnetic microparticle with a single internal magnetic core or consisting of multiple nanometer-sized cores of diameter s. b Schematic magnetization loop of an ensemble of ferromagnetic particles, showing magnetic hysteresis. c Schematic diagram of a microparticle superstructure in the presence of a magnetic field H. When the field is removed, the particles keep a remnant moment and the superstructure does not decompose generation of equally spaced arrays of columns of chains in a microchannel (Wang et al 1994;Sandre et al 1999;Hayes et al 2001a).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Furthermore, the study of confined self-assembly has revealed many interesting phenomena which depend on the nature of the confinement. [14][15][16][17][18][19][20][21] In the current study we will investigate the self-assembly of magnetorheological (MR) fluids in microfluidic confinement and the important role of channel topology.…”
Section: -4mentioning
confidence: 99%
“…However, the complex microfabrication processes and the limited field strength (0-100 mT) are the weak points of these devices. In contrast, passive magnetic microsystems use external macro-sized permanent magnets or electromagnets [25,27,38]. The process is simplified and larger magnetic fields (>0.5 T) and forces can be reached.…”
Section: Introductionmentioning
confidence: 99%